Salivary α-Amylase of Stem Borer Hosts Determines Host Recognition and Acceptance for Oviposition by Cotesia spp. (Hymenoptera, Braconidae) - Bichang'a, Gladys B.; Lage, Jean-Luc Da; Sambai, Kevin; Mule, Simon; Ru, Bruno Le; Kaiser, Laure; Juma, Gerald; Maina, Esther N.; Calatayud, Paul-André (Frontiers in Ecology and Evolution, 2018)
Foraging insect parasitoids use specific chemical cues to discriminate between host and non-host species. Several compounds have been identified in ‘host location and acceptance’. However, there is nothing known about the molecular variations in these compounds that account for host-range differences between parasitoid species. In a previous study, it was shown that during the host-finding process, the contact between the braconid Cotesia flavipes and its host is crucial, and that α-amylase of oral secretions from the host plays a key role for host acceptance and oviposition by the parasitoid. The present work investigated whether the variations in this enzyme could explain specific host recognition in different host-parasitoid associations. Different species and populations of the C. flavipes complex specialized on graminaceous lepidopteran stemborers were used. Electrophoresis of α-amylase revealed different isoforms that mediate oviposition acceptance and preference of the parasitoid for a specific host. This discovery opens new avenue to investigate evolutionary processes at play in chemically-mediated host specialization in the species-rich Cotesia genus.